A β-1, 3/1, 6-glucan from Durvillaea Antarctica inhibits tumor progression in vivo as an immune stimulator. (15th October 2019) - Su, Fan; Song, Qiaoling; Zhang, Chuanliang; Xu, Xiaohan; Li, Mengyuan; Yao, Dan; Wu, Lijuan; Qu, Xianjun; Guan, Huashi; Yu, Guangli; Yang, Jinbo; Zhao, Chenyang
Highlights: BG136 upregulates the phagocytosis activity of primary macrophages. BG136 increases the tumor infiltration of proinflammatory macrophages. BG136 modulates tumor microenvironment to proinflammatory and antitumoral status. BG136 decreases tumor burden in DLD1 xenograft and AOM-DSS induced cancer models. BG136 augments the antitumor effect of PD-1 antibody in B16 syngeneic tumor model. Abstract: β-glucans trigger the proinflammatory responses of innate immune cells to enhance the host defense. A variety of β-glucans were identified as strong immune stimulator and exerted antitumor activities. Our previous work indicates that a β-1, 3/1, 6-glucan (BG136) derived from marina alga Durvillaea antarctica promotes the proinflammatory responses in macrophage cell line RAW264.7. In the present study, we further explored its antitumor effects in vivo as an immune stimulator. The data shows that BG136 alone decreases the tumor burdens in DLD1 xenograft and AOM-DSS induced tumor models. BG136 also augments the antitumor effects of PD-1 antibody in B16 syngeneic tumor model. BG136 increases macrophage phagocytosis, enhances cytokine/chemokine secretion and modulates the systemic and intratumoral immune cell composition. Collectively, these data suggest that BG136 might act as an immune stimulator to exert antitumor effects in vivo .